Reinstatement of Cirsium tibeticum (Asteraceae, Cardueae) and the synonymization of C. argyracanthum under C. verutum - Jin, Zi-Chao; Chen, You-Sheng (Phytotaxa, 2025)
Based on our careful examination of herbarium specimens (including type material) and field observations in living populations, we demonstrate that Cirsium argyracanthum (Asteraceae, Cardueae) is a synonym of C. verutum, while C. tibeticum is readily distinguishable from C. verutum by its downward-sloping or nodding capitula and its phyllaries, which increase in length from the outermost to the innermost.